Membangun Innovative Work Behavior Pada Karyawan Generasi Millennial: Peran Transformational Leadership Dan Employee Engagement - Pratama Sivano Edsel; Dhyah Harjanti (.Universitas PGRI Adi Buana, 2024)
The generational shift in the workforce, from generation X to the millennial generation, requires company leaders to understand the behavior of millennial generation employees and adopt the leadership style used. This study analyzed whether transformational leadership and employee engagement can improve the innovative work behavior of millennial generation employees. This study used a quantitative approach, by surveying 167 millennial generation employees. The data was processed using Partial Least Square (PLS). The results showed that transformational leadership and employee engagement significantly increased innovative work behavior. Transformational leadership will foster engagement among employees, and in the end, will encourage the formation of innovative work behavior.